2-Azanorbornane-based amine organocatalyst for enantioselective aldol reaction of isatins with ketones. Issue 20 (15th November 2016) - Ogasawara, Ayumi; Subba Reddy, U.V.; Seki, Chigusa; Okuyama, Yuko; Uwai, Koji; Tokiwa, Michio; Takeshita, Mitsuhiro; Nakano, Hiroto
Graphical abstract: Abstract: Optically active 2-azanorbornane-based organocatalysts were designed and synthesized, and the catalytic activity of these catalysts in enantioselective aldol reactions of isatins with ketones was investigated. Among these catalysts, 2-azanorbornylmethanol showed the best catalytic activity to afford the corresponding aldol product in excellent chemical yield (up to 95%) and with moderate stereoselectivity (up to 64% ee, up to syn : anti  = 36:64). Abstract : (1 R, 3 S, 4 S )-2-Azabicyclo[2.2.1]heptane-3-e xo -diphenyl(trimethylsilyoxy)methane: C22 H29 NOSi [ α ]D 20  = +24.5 ( c 1.06, CHCl3 ) Source of chirality: ( R )-Phenylethylamine Absolute configuration: (1 R, 3 S, 4 S ) Abstract : (1 R, 3 S, 4 S )-2-Azabicyclo[2.2.1]heptane-3- exo -diphenylmethylamine: C19 H22 N2 [ α ]D 20  = +39.1 ( c 0.23, CHCl3 ) Source of chirality: ( R )-Phenylethylamine Absolute configuration: (1 R, 3 S, 4 S ) Abstract : (1 R, 3 S, 4 S )-2-[( R )-1-Phenylethyl]-2-azabicyclo[2.2.1]heptane-3- exo -diphenylmethylamine: C27 H30 N2 [ α ]D 22  = +90.9 ( c 0.11, CHCl3 ) Source of chirality: ( R )-Phenylethylamine Absolute configuration: (1 R, 3 S, 4 S )